2024
DOI: 10.1021/acs.energyfuels.3c04403
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Crude Oil Production in Microscopic Pores of CO2 Huff and Puff in Shale Oil Reservoirs

Shunyao Song,
Jiajing Chang,
Quansheng Guan
et al.

Abstract: The conversion coefficient C between relaxation time T 2 value and pore size was calibrated by a high-pressure mercury injection experiment, low-temperature nitrogen adsorption experiment, and NMR experiment for clarifying the effect of CO 2 huff and puff on the production characteristics of crude oil in shale micronano pores. Then, the effects of huff and puff rounds, the soaking time, and injection pressure on the seepage law of crude oil in shale pores from the microscopic scale were studied. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Relevant investigations have shown that supercritical carbon dioxide (SC-CO 2 ) can significantly enhance the recovery of shale reservoirs. When the pressure and temperature of CO 2 reach a certain condition (generally P ≥ 7.38 MPa, T ≥ 31.1 °C), it will enter the supercritical phase. Thanks to its high density, minimal viscosity, and excellent diffusivity, supercritical carbon dioxide (SC-CO 2 ) easily mixes with crude oil and can effectively lower its viscosity. This makes it easier for more shale oil to flow to the wellbore and efficiently enhances the recovery. , Meanwhile, CO 2 used can also be sequestered in shale reservoirs in the form of dissolution, trapping, and mineralization. …”
Section: Introductionmentioning
confidence: 99%
“…Relevant investigations have shown that supercritical carbon dioxide (SC-CO 2 ) can significantly enhance the recovery of shale reservoirs. When the pressure and temperature of CO 2 reach a certain condition (generally P ≥ 7.38 MPa, T ≥ 31.1 °C), it will enter the supercritical phase. Thanks to its high density, minimal viscosity, and excellent diffusivity, supercritical carbon dioxide (SC-CO 2 ) easily mixes with crude oil and can effectively lower its viscosity. This makes it easier for more shale oil to flow to the wellbore and efficiently enhances the recovery. , Meanwhile, CO 2 used can also be sequestered in shale reservoirs in the form of dissolution, trapping, and mineralization. …”
Section: Introductionmentioning
confidence: 99%